2004
DOI: 10.1021/ef049792z
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Interactions between Reservoir Brine and CO2at High Pressures and Elevated Temperatures

Abstract: In this paper, an experimental technique has been developed to study the interfacial interactions of the reservoir brine-CO 2 system at high pressures and elevated temperatures. Using the axisymmetric drop shape analysis (ADSA) for the pendant drop case, this new technique makes it possible to determine the interfacial tension (IFT) and visualize the interfacial interactions between the reservoir brine and CO 2 under practical reservoir conditions. More specifically, the dynamic IFT between the reservoir brine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 25 publications
6
81
0
Order By: Relevance
“…At these conditions, pure CO 2 will be in a supercritical state (T c ~ 304.13 K and P c ~ 7.38 MPa) and with densities higher than 662 kg·m -3 . Due to its key role in the design of the processes mentioned above, many studies have been conducted on the experimental measurement of the IFT of the CO 2 /H 2 O system during the last two decades [6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. In most of these studies the pendant drop method has been used to perform these measurements over a wide range of experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…At these conditions, pure CO 2 will be in a supercritical state (T c ~ 304.13 K and P c ~ 7.38 MPa) and with densities higher than 662 kg·m -3 . Due to its key role in the design of the processes mentioned above, many studies have been conducted on the experimental measurement of the IFT of the CO 2 /H 2 O system during the last two decades [6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. In most of these studies the pendant drop method has been used to perform these measurements over a wide range of experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Chiquet et al (2007a) state that the maximum allowable CO 2 storage pressure may only exceed initial reservoir pressure by a fraction. Correlations of pressure and temperature with interfacial tension and wetting angle and their effect on CO 2 storage capacities have been investigated by Yang et al (2005), Chalbaud et al (2006Chalbaud et al ( , 2009 and Chiquet et al (2007a,b). In addition Shah et al (2008) demonstrated that the water-wettability of caprocks can vary in the presence non-wetting gas (CO 2 or H 2 S) and the mineral substance of the solid phase.…”
Section: Introductionmentioning
confidence: 99%
“…When the water content was higher, the dynamic IFT is almost constant from the very beginning. This means that the pendant drop and CO 2 can quickly reach the equilibrium state [10]. Fig.…”
Section: A the Dynamic Pendant Oil Drop Analysismentioning
confidence: 92%